The Relative Performance of Real Estate Marketing Platforms: MLS versus FSBOMadison.com - Hendel, Igal; Nevo, Aviv; Ortalo-Magné, François (American Economic Review, 2009)
We compare house sales on a For-Sale-By-Owner (FSBO) platform to Multiple Listing Service (MLS) sales and find that FSBO precommission prices are no lower, but that FSBO is less effective in terms of time to sell and probability of a sale. We do not find direct evidence of the importance of network size as a reason for the lower effectiveness of FSBO. We do find evidence of endogenous platform differentiation: patient sellers use FSBO while patient buyers transact more often on the MLS (where they avoid patient sellers). We discuss the implications for platform competition, two-sided markets, and welfare. (JEL L85, M31, R31)